An alternative method for correcting fluorescence quenching - L. Biermann; C. Guinet; M. Bester; A. Brierley; L. Boehme (Ocean Science, 2015)
Under high light intensity, phytoplankton protect their photosystems from bleaching through non-photochemical quenching processes. The consequence of this is suppression of fluorescence emission, which must be corrected when measuring in situ yield with fluorometers. We present data from the Southern Ocean, collected over five austral summers by 19 southern elephant seals tagged with fluorometers. Conventionally, fluorescence data collected during the day (quenched) were corrected using the limit of the mixed layer, assuming that phytoplankton are uniformly mixed from the surface to this depth. However, distinct deep fluorescence maxima were measured in approximately 30% of the night (unquenched) data. To account for the evidence that chlorophyll is not uniformly mixed in the upper layer, we propose correcting from the limit of the euphotic zone, defined as the depth at which photosynthetically available radiation is ~ 1% of the surface value. Mixed layer depth exceeded euphotic depth over 80% of the time. Under these conditions, quenching was corrected from the depth of the remotely derived euphotic zone Zeu, and compared with fluorescence corrected from the depth of the density-derived mixed layer. Deep fluorescence maxima were evident in only 10% of the day data when correcting from mixed layer depth. This was doubled to 21% when correcting from Zeu, more closely matching the unquenched (night) data. Furthermore, correcting from Zeu served to conserve non-uniform chlorophyll features found between the 1% light level and mixed layer depth.